Transforming Information Systems Management: A Modern Approach to Digital Evolution - Dipteshkumar Madhukarbhai Patel, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative shift in information systems management from traditional operational support functions to strategic business enablers in today's digital landscape. Organizations that successfully modernize their information systems approach can achieve significant competitive advantages through enhanced decision-making capabilities, operational efficiencies, and customer experiences. The transformation encompasses several interconnected dimensions including cloud adoption, big data analytics, artificial intelligence integration, cybersecurity enhancement, data governance implementation, agile methodologies adoption, and strategic digital alignment. Despite compelling benefits, organizations face substantial challenges in cultural resistance, technical integration, security risk mitigation, and resource allocation that must be systematically addressed. The evolving role of information systems leadership requires new competencies in strategic planning, technology evaluation, and change management to effectively navigate this transformation journey and deliver sustainable business value in increasingly competitive environments.
Keywords: Agile Methodologies; Cloud Adoption; Cybersecurity Frameworks; Digital Transformation; Information Systems Management